1997
DOI: 10.1164/ajrccm.155.2.9032192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled and oral glucocorticoids on inflammatory indices in asthma and COPD.

Abstract: The role of glucocorticoids in the treatment of chronic obstructive pulmonary disease (COPD) is controversial. We have previously described high numbers of neutrophils and high concentrations of the inflammatory cytokines interleukin-8 (IL-8) and tumor necrosis factor-alpha (TNF-alpha), and of the cell activation markers eosinophil cationic protein (ECP), eosinophil peroxidase (EPO), myeloperoxidase (MPO), and human neutrophil lipocalin (HNL) in COPD patients as compared with controls, and have postulated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
278
1
17

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(314 citation statements)
references
References 20 publications
17
278
1
17
Order By: Relevance
“…In COPD, inflammation is not suppressed by corticosteroids and there is no reduction in inflammatory cells, cytokines, or proteases in induced sputum, even with oral corticosteroids (63,64). Corticosteroids do not suppress neutrophilic inflammation in the airways, and corticosteroids may prolong the survival of neutrophils (65).…”
Section: Corticosteroid Resistance In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…In COPD, inflammation is not suppressed by corticosteroids and there is no reduction in inflammatory cells, cytokines, or proteases in induced sputum, even with oral corticosteroids (63,64). Corticosteroids do not suppress neutrophilic inflammation in the airways, and corticosteroids may prolong the survival of neutrophils (65).…”
Section: Corticosteroid Resistance In Copdmentioning
confidence: 99%
“…There is a striking reduction in the activity and expression of HDACs in the peripheral lung of patients with COPD (68). Even in patients with COPD who have stopped smoking, the steroid resistance persists (63,64), and these patients are known to have continuing oxidative stress (69).…”
Section: Corticosteroid Resistance In Copdmentioning
confidence: 99%
“…(50,51). This in particular has been shown for patients with asthma, chronic obstructive pulmonary disease (COPD) and cystic fibrosis (8,9,19,50,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). The greatest problem with sputum measurement is to obtain sputum, as sputum production has to be induced in those subjects who are not spontaneous producers.…”
Section: Various Cellsmentioning
confidence: 99%
“…The numbers of eosinophil granulocytes in sputum have been estimated in this way by the measurement of ECP in the extract and there is a large number of publications showing that the numbers of eosinophils measured in this way are well correlated to disease activity in asthma and how the numbers are reduced as a consequence of corticosteroid treatment. In patients with COPD it has been shown that treatment success with corticosteroids is related to the eosinophilic inflammation in the bronchi as measured by sputum ECP (60,70). An interesting alternative to sputum could be the measurement in saliva, as we showed recently that asthmatics had significantly raised levels of ECP in saliva and that the levels were reduced by corticosteroid treatment (71).…”
Section: Various Cellsmentioning
confidence: 99%
“…Therefore, it is highly beneficial to avoid exposure to the allergen. Use of inhaled corticosteroids is very effective medication (4,6). The agents act via various pharmacological effects to suppress production of inflammatory cytokines as well as the function of eosinophils and lymphocytes, and to enhance formation of anti-inflammatory substances and expression of p-adrenergic receptors.…”
Section: ) Genetic Factorsmentioning
confidence: 99%